PENGARUH PEMAHAMAN PERATURAN PAJAK DAN KESADARAN WAJIB PAJAK TERHADAP KEPATUHAN WAJIB PAJAK (Studi Kasus Wajib Pajak Badan Klien Fa. HLP Consultant) - Rusmanto -; Januarti Alpisah (Dinamika Ekonomi - Jurnal Ekonomi dan Bisnis, 2018)
Abstract, This research aims to prove the effect of understanding tax regulation and taxpayer awareness to the taxpayer's compliance of Fa Client's Agency. HLP Consultant. Population in this research is all Taxpayer Agency which become client at Fa. HLP Consultant amounts to 452 corporate taxpayers. The number of samples taken using the rule of thumb as many as 100 corporate taxpayers. The results prove the understanding of tax rules partially affect the compliance of Taxpayers, Taxpayer Consciousness partially influence the compliance of Taxpayers, and Understanding tax regulations and awareness of Taxpayers simultaneously affect the compliance of Taxpayers.